Single crystal growth from separated educts and its application to lithium transition-metal oxides: Data archive - Williams, S; Johnson, R; Coldea, R (University of Oxford, 2016)
the deposited package contains single-crystal x-ray diffraction data from which the crystal structure of alpha-Li2IrO3 was refined.